Bevacizumab in Retinopathy of Prematurity : Concerns and adverse effects - Sharma, Anuj; Shetty, Adheesh; Reddy, Y.C. Venu Gopal (Nepalese Journal of Ophthalmology, 2020)
Retinopathy of prematurity (ROP) ranks as one of the leading causes of blindness in the paediatric age group, the incidence of which is increasing in developing countries as the economy strengthens and healthcare practices improve. As a vasoproliferative disorder affecting premature neonates VEGF is said to play a vital role in the pathogenesis of ROP. Evidence of the efficacy of anti-VEGF agents in treatment of ROP have been seen in literature since early 2007 with most published reports being either case studies or small case series. The only randomised controlled trial in this regard was the BEAT-ROP study which was published in 2011. However, even in that study the adverse effects of Bevacizumab were not analysed. This review aims to discuss the complications prior to the blanket administration of intravitreal bevacizumab in the management of ROP.